2008
DOI: 10.1002/cncr.23494
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative assessment enables the early diagnosis and successful treatment of lymphedema

Abstract: A short trial of compression garments effectively treated subclinical LE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
420
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 413 publications
(431 citation statements)
references
References 62 publications
8
420
0
3
Order By: Relevance
“…This latter recommendation is based on research published subsequent to the 2001 CPG, in which it was shown that volume measurements using an opto-electric volumeter were especially sensitive to subtle changes in upper limb volume. 67 If an opto-electric volumeter (perometer) is available, albeit not common in clinical practice, it should be used in place of arm circumference measures. Another measure that shows promise in measuring early, fluid-based changes is bioimpedance spectroscopy, which is described in the Australian lymphedema guideline.…”
Section: Syntheses Of Guideline Recommendationsmentioning
confidence: 99%
“…This latter recommendation is based on research published subsequent to the 2001 CPG, in which it was shown that volume measurements using an opto-electric volumeter were especially sensitive to subtle changes in upper limb volume. 67 If an opto-electric volumeter (perometer) is available, albeit not common in clinical practice, it should be used in place of arm circumference measures. Another measure that shows promise in measuring early, fluid-based changes is bioimpedance spectroscopy, which is described in the Australian lymphedema guideline.…”
Section: Syntheses Of Guideline Recommendationsmentioning
confidence: 99%
“…Traditionally, lymphedema has been clinically diagnosed by healthcare professionals' observations of swelling, and has often arbitrarily been defined in research as a 2-cm increase in limb girth, a 200-mL or more increase in limb volume, or a 5% or greater limb volume change Cormier et al, 2009;Stout et al, 2008). Inconsistency in the criteria defining lymphedema and the use of different measures has posed tremendous difficulty in accurately diagnosing lymphedema (Armer & Stewart, 2005).…”
Section: Diagnosis Of Breast Cancer-related Lymphedemamentioning
confidence: 99%
“…The advent of infra-red perometry (also called optoelectronic volumetry), such as the perometer 350S (Juzo, Cuyahoga Falls, OH), enables reliable and accurate detection of 3% limb volume change (LVC) (Cormier et al, 2009;Stout et al, 2008). The perometer works in much the same manner as computed tomography but uses infrared light instead of X-rays (Petlund, 1991).…”
Section: Infra-red Perometrymentioning
confidence: 99%
See 2 more Smart Citations